ANALISIS KESULITAN SISWA SMK KELAS X DI KOTA BANDUNG DALAM MENYELESAIKAN SOAL MATERI BARISAN DAN DERET - Abdul Karim, Raisya Silvi; Novtiar, Chandra (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This article aims to describe the results of the analysis of the difficulties of class X SMK students in Bandung City in solving the question of the sequence and series material. This type of research is a case study. The subjects of this study were 36 students of class X SMK Kencana Bandung. The research instrument consisted of 5 questions in the sequence and series material test. The data analysis technique used is the data collection technique with the documentation method in the form of student test results in sequence and series. The results showed that only question number 4 had the percentage of mastery of the material below 75%, it could be said that some students still had difficulty solving question number 4 which had indicators of evaluating sequence and series. From the results of the analysis, it was concluded that the difficulty of X SMK students in solving the sequence and series problems lies in the indicators of evaluating sequences and series, that is: (1) Students have difficulty applying the formula for the n-syllable of an arithmetic sequence; (2) Students have difficulty identifying important information from artithmetic sequence story questions and (3) Students find it difficult to describe the formula for the n-syllable of arithmetic sequence to get the first syllable.